Performance Optimization of Unit Turjawali Sat Samapta Polres Grobogan to Realize Conducive Peace and Order in Society Through Patrol Activities - Rohadi, Deny Ariyadi (Advances in Police Science Research Journal, 2024)
The research was conducted at the Polres Grobogan to describe the performance of the Unit Turjawali Sat Samapta Polres Grobogan through patrol activities in_order to create a conducive community peace and order in society. The research was conducted using a qualitative method of the Field Research type, which was supported by data collection techniques in the form of observation, interviews, and documentation studies. This study uses Organizational Resource Theory, Management Theory, SWOT Analysis Theory, Optimization Concept, and Patrol Concept, in describing the problems and solutions to these problems. The final_results of this study found a gap or several conditions that were not following what they should have been, on base of Patrols concept, however those case make the Patrols not optime yet. This is influenced by various internal and external factors. Analysis of factors as well as appropriate problem-solving steps needed, in spite of organizational resource factors or management system of Patrols, to optimize the performance of the Unit Turjawali Sat Samapta Polres Grobogan to create conducive peace and order in society through patrol activities.